Implementasi Metode Cerita Tentang Kisah Rasulullah Dalam Menanamkan Akhlak Menuntut Ilmu Sesuai Al-Qur’an Pada Siswa MTsN 2 Kota Bengkulu - Salsabila, Dinah Yusiana; Demi Susanti; Dola Risma Ayu; Yola Oktri Hardi; Nur Royani Ahlina (Gayaku Publisher, 2025)
This journal discusses the implementation of the Apostle's story method as an educational strategy in instilling the morals of seeking knowledge according to the Koran in MTsN 2 Bengkulu City students. The Rasulullah story method is an approach that utilizes stories from the life of the Prophet Muhammad. as a source of inspiration and moral lessons. This research aims to identify the effectiveness of this method in shaping students' Islamic behavior and its impact on their understanding of Islamic ethical and moral values ​​in studying. This research uses a qualitative approach with observation, interviews and document analysis methods. The results of the research show that the use of the Apostle's story method has had a positive impact in increasing students' understanding of the morals of studying according to the Al-Qur'an. Students who engage in learning with this method show an increase in positive behavior, such as honesty, humility, and empathy.Stories about the Prophet Muhammad. provide students with real examples of how to apply Islamic teachings in everyday life. Apart from that, this method also helps students understand Islamic moral and ethical principles in more depth. In conclusion, the implementation of the Rasulullah story method in Islamic education at MTsN 2 Bengkulu City has proven its effectiveness in instilling Islamic morals in students. The results of this research provide encouragement for Islamic educational institutions to consider more closely the use of the Apostle's story method in learning as a means of strengthening moral education according to the Al-Qur'an.